Preparation of open-cell polymer foams by CO2 assisted foaming of polymer blends. (4th May 2016) - Kong, Wei-long; Bao, Jin-Biao; Wang, Jia; Hu, Guo-Hua; Xu, Yang; Zhao, Ling
Abstract: This paper reports on a novel process for preparing open-cell polymer foams which consists in (1) blending a desired polymer with one which is much more CO2 -philic and which is the dispersed phase, (2) tuning the sea-island type of morphology of the polymer blend to a co-continuous type by selectively swelling the CO2 -philic polymer with CO2 saturation, and (3) selectively foaming the CO2 -philic polymer by CO2 depressurization. More specifically, a blend composed of 70% of isotactic polypropylene (PP) and 30% of a copolymer of ethylene-propylene-diene monomer (EPDM) is chosen to show the working principle and potential of the above process. PP is a desired polymer and EPDM a CO2 -philic one. During the CO2 saturation, the initially sea-island type of morphology of the PP/EPDM (70/30) blend evolves into a more or less co-continuous one due to the much more CO2 -philic nature of the EPDM. Upon CO2 depressurization, foaming takes place primarily in the EPDM phase, leading to open cells. To achieve open-cells for the PP/EPDM (70/30) blend, it is necessary to search for an optimum CO2 saturation pressure and temperature window. Within this window, the cell size and the expansion ratio are in the range of 1.5–17.5 μm and 1.5–6.6, respectively. Tensile results show that the elongation at break of the CO2 saturated and foamed PP/EPDM blends is higher than that of the un-treated one, indicating that the co-continuous morphology of the PP/EPDM blend improves its toughness. Moreover, compression results indicate that the open-cell foams exhibit good flexibility and elasticity. Graphical abstract: Highlights: Phase transition was induced by CO2 saturation. Open-cell foams were prepared by CO2 foaming of co-continuous polymer blends. Mechanical properties were investigated.